Patient Age Is Significantly Related to Distant Metastasis of Papillary Thyroid Microcarcinoma - Huang, Hui; Xu, Siyuan; Wang, Xiaolei; Liu, Shaoyan; Liu, Jie (Frontiers in Endocrinology, 2021)
Objective: Distant metastasis in papillary thyroid microcarcinoma (PTMC) is rare but fatal and its relationship with patient age remains unclear. The objective of this study was to examine the association between age at diagnosis and metachronous distant metastasis in PTMC. Methods: Consecutive patients who underwent thyroidectomy for PTC measuring 10 mm or less at a tertiary hospital from January 2000 to December 2016 were enrolled. Patients who had evidence of distant metastasis at diagnosis, or underwent postoperative radioiodine (RAI) ablation or followed up less than 12 months were excluded. A Cox proportional hazards model with restricted cubic splines (RCS) were applied to examine the association between age at diagnosis and distant metastasis. Results: A total of 4749 patients were evaluated. The median age was 44 years (range, 8–78 years), and 3700 (78%) were female. After a median follow-up of 65 months, 21 distant metastases (20 lung, 1 liver) were recognized. A univariate Cox proportional model using a 5-knot RCS revealed a significant overall (p=0.01) and a potential nonlinear association (p=0.08) between distant metastasis and age at diagnosis. In multivariate analysis, age at diagnosis, extrathyroidal extension (ETE) and lymph node metastasis (pN+) were independent risk factors for distant metastasis. Compared with the middle-aged group (30–45 years old), younger and older patients had a higher risk of distant metastasis (HR, 95%CI, p value, age≤30, 4.54(0.91–22.60), 0.06, age>45, 6.36(1.83–22.13), <0.01). Conclusion: Age at diagnosis is associated with metachronous distant metastasis of PTMC, and patients with younger or older age have a higher risk of distant metastasis than middle-age patients.